Advanced nonlinear control of complex power systems - Li, Hong Yin (2008)
Nowadays, advanced controller design is called upon to guarantee the secure and reliable operation of power systems. To meet this requirement, this work proposed three control strategies: 1) robust coordinated transient stability and voltage regulation enhancement (CTSVRE) control of generator excitation systems, which enhances both transient stability and post-fault voltage regulation; 2) robust coordinated control of AC/DC power systems with overlapping decomposition, which coordinates both AC system control and DC system control from a systematic standpoint; 3) robust constrained control of generator excitation systems, which considers input saturation from the beginning of controller design. The designed controllers are tested by numerical simulation using PSCAD/EMTDC software. Their performances are compared with those of other controllers and evaluated using different cases. Results show that the proposed control strategies are quite effective.